Moduli spaces of polynomials in two variables - Fernández de Bobadilla, Javier, 1973- (Memoirs of the American Mathematical Society, 2005)
Introduction Automorphisms of the affine plane A partition on $\mathbb{C}[x, y]$ The geometry of the partition The action of Aut$(\mathbb{C}^2)$ on $\mathbb{C}[x, y]$ The moduli problem The moduli spaces Appendix A. Canonical orders Bibliography.